Comparative study of intrathecal fentanyl, tramadol, clonidine mixed with bupivacaine for peri and post operative pain relief in lower limb and lower abdominal surgery - Avinash, Raja; Singh, Praveen Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Pain relief is of paramount importance in patients undergoing surgery during perioperative and post-operative period. After effective pain relief a smoother post-operative period and early discharge from the hospital is anticipated. Intrathecal and epidural narcotics have been widely used to relieve pain and provide post-operative analgesia. Here three drugs tramadol, fentanyl, and clonidine used as adjuvant with bupivacaine in intrathecal injection for post-operative pain relief and comparative study had been done. Methods: After the study protocol was approved by the Ethical clearance committee of the DMCH, Laheriasarai, Bihar. Study design was prospective, randomized and double-blind techniques. A group of 80 patients undergoing lower abdominal and lower limb surgery were included in the study. Every patient was fully explained about the anaesthesia and surgical procedure before inclusion in the study. The patients were in the (25-65) years age group and belonged to the American Society of Anaesthesiologist (ASA) physical status class I-II and scheduled for lower abdominal and lower limbs surgery were randomly allocated to four groups with equal number: group B [Bupivacaine (35)% 3 cc + 0.4 cc normal saline], group BT [Bupivacaine (5)% 3 cc + 25 mg tramadol], BC [Bupivacaine (0.5)% 3 c.c + 30 μg clonidine], BF [Bupivacaine (0.5)% 3 c.c + 20 μg fentanyl]. All additive drugs used intrathecally were preservative free. All intrathecal punctures were performed in the lateral (Right or Left) position with a (25G) Quinke needle, using the midline approach at the L3-L4 intervertebral space. Results: The study revealed that administration of additives in group BC and group BF did prolong analgesia. In group B, duration of analgesia and mean duration of rescue analgesic requirement was (3.57±0.45) hrs. For group BC it was (9.47±0.85) hrs, for group BF (7.6±1.14) hrs, for group BT (3.72±0.42) hrs. Conclusions:Addition of adjuvants (Fentanyl, Clonidine) to intrathecal bupivacaine for perioperative pain relief does prolong postoperative analgesia and improves the intraoperative quality of analgesia than bupivacaine alone. Background: Pain relief is of paramount importance in patients undergoing surgery during perioperative and post-operative period. After effective pain relief a smoother post-operative period and early discharge from the hospital is anticipated. Intrathecal and epidural narcotics have been widely used to relieve pain and provide post-operative analgesia. Here three drugs tramadol, fentanyl, and clonidine used as adjuvant with bupivacaine in intrathecal injection for post-operative pain relief and comparative study had been done. Methods: After the study protocol was approved by the Ethical clearance committee of the DMCH, Laheriasarai, Bihar. Study design was prospective, randomized and double-blind techniques. A group of 80 patients undergoing lower abdominal and lower limb surgery were included in the study. Every patient was fully explained about the anaesthesia and surgical procedure before inclusion in the study. The patients were in the (25-65) years age group and belonged to the American Society of Anaesthesiologist (ASA) physical status class I-II and scheduled for lower abdominal and lower limbs surgery were randomly allocated to four groups with equal number: group B [Bupivacaine (35)% 3 cc + 0.4 cc normal saline], group BT [Bupivacaine (5)% 3 cc + 25 mg tramadol], BC [Bupivacaine (0.5)% 3 c.c + 30 μg clonidine], BF [Bupivacaine (0.5)% 3 c.c + 20 μg fentanyl]. All additive drugs used intrathecally were preservative free. All intrathecal punctures were performed in the lateral (Right or Left) position with a (25G) Quinke needle, using the midline approach at the L3-L4 intervertebral space. Results: The study revealed that administration of additives in group BC and group BF did prolong analgesia. In group B, duration of analgesia and mean duration of rescue analgesic requirement was (3.57±0.45) hrs. For group BC it was (9.47±0.85) hrs, for group BF (7.6±1.14) hrs, for group BT (3.72±0.42) hrs. Conclusions: Addition of adjuvants (Fentanyl, Clonidine) to intrathecal bupivacaine for perioperative pain relief does prolong postoperative analgesia and improves the intraoperative quality of analgesia than bupivacaine alone.